2008
DOI: 10.1097/bpo.0b013e318173f795
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Injuries After Traumatic Patellar Dislocation in Adolescents

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Kepler studied 44 children and adolescents after acute LPD, and he found that the prevalence rate of the MPFL injury was 94%, including 61% of the MPFL disruption occurred at its PAT, 12% occurred at the FEM, 12% occurred at the FEM and PAT, 9% occurred at the MID and either PAT or FEM [3]. The finding of the MPFL will more likely rupture at the PAT after an acute LPD in children and adolescents was also supported by several studies [4][5][6][7]. However, Balcarek evaluated a series of 22 children and adolescents after acute LPD and the MPFL injury was identified in 20 patients (90.9%), including two cases (10%) of tear at PAT, three cases (15%) of injury at MID, eight cases (40%) of injury at FEM and seven cases (35%) of injury at the FEM and the PAT [8].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Kepler studied 44 children and adolescents after acute LPD, and he found that the prevalence rate of the MPFL injury was 94%, including 61% of the MPFL disruption occurred at its PAT, 12% occurred at the FEM, 12% occurred at the FEM and PAT, 9% occurred at the MID and either PAT or FEM [3]. The finding of the MPFL will more likely rupture at the PAT after an acute LPD in children and adolescents was also supported by several studies [4][5][6][7]. However, Balcarek evaluated a series of 22 children and adolescents after acute LPD and the MPFL injury was identified in 20 patients (90.9%), including two cases (10%) of tear at PAT, three cases (15%) of injury at MID, eight cases (40%) of injury at FEM and seven cases (35%) of injury at the FEM and the PAT [8].…”
Section: Discussionmentioning
confidence: 57%
“…Although the evaluation of MPFL tears after LPD in children and adolescents has been described in a few papers, there still remains some conflicts about the main rupture location of the MPFL [3][4][5][6][7][8][9]. Although there were some studies about articular cartilage lesions of the inferomedial patella and the lateral femoral condyle [4,5,[10][11][12][13][14][15][16][17][18][19][20][21], there were no studies concentrating on the correlations between the injury patterns of the MPFL and articular cartilage lesions of the lateral femoral condyle in children and adolescents.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Ultrasound evaluation following acute patellar dislocation in adolescent patients has also been shown to be effective in determining the extent and location of soft tissue and bony injuries as well as identification of intra-articular loose bodies. 43 Ultrasound evaluation has potential to play a larger role in initial evaluation of patellar dislocation given its cheaper cost, portability, and ability to dynamically assess anatomy.…”
Section: Evaluation Of First-time Patellofemoral Dislocationmentioning
confidence: 99%
“…1,2 Patellar articular cartilage injuries can range from minor cartilaginous fissures to large, displaced osteochondral fractures. [1][2][3] When significant fractures of the medial patellar articular surface are present, fracture fixation with open reduction and internal fixation or loose body fragment removal is indicated. 4,5 The critical fragment size that mandates fixation has not been established, but fragments that are large enough to accept fixation hardware can presumably be fixed.…”
mentioning
confidence: 99%